Plasma metabolites associated with biopsychosocial parameters in overweight/obese women with severe knee osteoarthritis - Lisboa, Fabiola Socorro Silva; Benevento, Enzo Martins; Kaneko, Luisa Oliveira; Bertolucci, Vanessa; Rosini Silva, Álex Ap.; Sardim, André Cabral; Ruiz, Valter Ferreira; dos Reis, Ivan Gustavo Masseli; Porcari, Andreia M.; Messias, Leonardo Henrique Dalcheco (Frontiers in Cell and Developmental Biology, 2024)
Obesity aligned with quadriceps muscle weakness contributes to the high incidence of knee osteoarthritis (KOA), which is prevalent in women. Although molecular signatures of KOA have been suggested, the association between biopsychosocial responses and the plasma metabolomic profile in overweight/obese women with KOA remains in its early stages of investigation. This study aims to associate the plasma metabolome with biopsychosocial parameters of overweight/obese women diagnosed with KOA. Twenty-eight overweight/obese women (Control-n=14; KOA-n=14) underwent two visits to the laboratory. Functional tests and questionnaires assessing biopsychosocial parameters were administered during the first visit. After 48 hours, the participants returned to the laboratory for blood collection. Specific to the KOA condition, the Numerical Pain Rating Scale (NPRS), Tampa Scale for Kinesiophobia (TSK), and Knee injury and Osteoarthritis Outcome Score (KOOS) were applied. Thirteen molecules were different between groups, and four correlated with KOA's biopsychosocial parameters. DG 22:4-2OH and gamma-Glutamylvaline were inversely associated with KOSS leisure and TSK score, respectively. LysoPE 18:0 and LysoPE 20:5 were positively associated with KOSS symptoms and TSK score, respectively. While the correlations of LysoPE 18:0 and gamma-Glutamylvaline are supported by existing literature, this is not the case for DG 22:4-2OH and LysoPE 20:5. Further studies are recommended to better elucidate these correlations before dismissing their potential involvement in the biopsychosocial factors of the disease.